EFFECTS OF ROBOTICS ON 21st CENTURY SKILLS - Khanlari, Ahmad (European Scientific Journal, ESJ, 2013)
Research indicates that robotics influences many educational aspects and has a great impact on students’ abilities and skills. The present study seeks to examine teachers' perceptions of the effects of robotics on students’ personal skills and the analysis reveals four major themes in this regard. A comparison between these themes and the 21st century learning framework shows that robotics is an effective tool for improving 21st century skills, including students’ creativity, collaboration and team-working, self-direction, communication skills, social and cross-cultural skills, and social responsibilities. Therefore, robotics can be used as an effective tool to prepare students for the 21st century.